2019
DOI: 10.1111/dom.13912
|View full text |Cite
|
Sign up to set email alerts
|

Increased proportion of time in hybrid closed‐loop “Auto Mode” is associated with improved glycaemic control for adolescent and young patients with adult type 1 diabetes using the MiniMed 670G insulin pump

Abstract: The Medtronic MiniMed 670G system delivers insulin to patients with type 1 diabetes mellitus (T1DM) using either its hybrid closed‐loop (HCL) “Auto Mode” feature or an open‐loop mode. In this retrospective, cross‐sectional analysis, we quantified the association between time in Auto Mode and both haemoglobin A1c (HbA1c) and time in range (TIR, sensor glucose 70–180 mg/dL) among 96 paediatric and young adult patients with T1DM. The median percentage time in Auto Mode was 38.5% (interquartile range 0%–64%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 9 publications
4
32
0
Order By: Relevance
“…This high percentage use of automation and no dropout rates can be attributed to the specific selection/initiation protocol including the initial use of the system as a sensor alone for 7 days, although the relative contribution of each component cannot be determined from the study. The study confirmed previous conclusions, that increased Auto Mode usage is associated with lower HbA1c and increased TIR, resulting in that patients with both higher sensor wear times and increased Auto Mode usage had incrementally lower HbA1c than patients with lower sensor wear time and less Auto Mode usage [17]. Our data showed high Auto Mode usage of 85.6% at 1 year, which is higher than 51% at 6 months after HCL initiation [13].…”
Section: Discussionsupporting
confidence: 90%
“…This high percentage use of automation and no dropout rates can be attributed to the specific selection/initiation protocol including the initial use of the system as a sensor alone for 7 days, although the relative contribution of each component cannot be determined from the study. The study confirmed previous conclusions, that increased Auto Mode usage is associated with lower HbA1c and increased TIR, resulting in that patients with both higher sensor wear times and increased Auto Mode usage had incrementally lower HbA1c than patients with lower sensor wear time and less Auto Mode usage [17]. Our data showed high Auto Mode usage of 85.6% at 1 year, which is higher than 51% at 6 months after HCL initiation [13].…”
Section: Discussionsupporting
confidence: 90%
“… 20 Prior studies of different systems have pointed to the need to keep closed-loop automation active, with improved TIR and decreased A1c correlating with time spent with closed-loop automation active. 21 A considerable amount of literature has been developed on how to help patients with diabetes use AID systems, particularly related to keeping closed-loop automation active. 22 , 23 Control-IQ technology has only one reason for automation to cease (loss of CGM connectivity for 20 or more minutes), and automatically resumes automation as soon as valid CGM values are received with no need for the user to switch on or activate automation in any way.…”
Section: Resultsmentioning
confidence: 99%
“…Some education is common to most novel diabetes technology, for example, the need to count carbohydrates and deliver meal bolus with food. In addition there is also a need for specific education with hybrid closed‐loop systems, for example, how to deal with and minimize "automode exits", how to deal with connection problems software issues and updates, and how to safely use standard sensor‐augmented pump therapy at times when closed loop is not working for whatever reason 29,30 . Users and healthcare professionals also need to be educated about interpretation of data outputs from various closed‐loop software systems and how to adjust existing pump settings based on closed‐loop performance.…”
Section: Discussionmentioning
confidence: 99%